The Disaster of the Third Princess Essays on The Tale of Genji - Tyler, Royall (Asian Studies Series Monograph, 2009)
These seven essays by the most recent English translator of The Tale of Genji emphasize three major interpretive issues. What is the place of the hero (Hikaru Genji) in the work? What story gives the narrative underlying continuity and form? And how does the closing section of the tale (especially the ten "Uji chapters") relate to what precedes it? Written over a period of nine years, the essays suggest fresh, thought-provoking perspectives on Japan's greatest literary classic.